2010
DOI: 10.5539/jas.v2n4p52
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Farm Record Keeping Behaviour among Small-Scale Poultry Farmers in the Ga East Municipality

Abstract: The study sought to investigate the farm record keeping behaviour among small-scale poultry farmers in the Ga East Municipality. Data was collected by the use of the simple random sampling technique. All the poultry farmers interviewed kept at least production and financial records. The chi-square test of independence showed that farm record keeping was independent of age, educational level, experience in poultry farming, farmer status, number of birds owned by respondents and respondents' membership of a farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
1
14
0
Order By: Relevance
“…In addition, farmers receive assistance from TIST in accessing formal credit. This kind of program not only improves farmers' human capital, especially skills related to record-keeping and farm management, but also introduces carbon certification as an additional source of income (Tham-Agyekum et al 2010;Pagiola et al 2005). EES have led to improvements in/and diversification of farm revenues among adopting farmers (Kagwiria 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, farmers receive assistance from TIST in accessing formal credit. This kind of program not only improves farmers' human capital, especially skills related to record-keeping and farm management, but also introduces carbon certification as an additional source of income (Tham-Agyekum et al 2010;Pagiola et al 2005). EES have led to improvements in/and diversification of farm revenues among adopting farmers (Kagwiria 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, several other countries in the region are yet to make such steps especially if they are located in conflict regions. Apart from providing information to farmers, good records and data can enhance access to agricultural credit which remains a major challenge for many farmers in Africa (Denkyirah et al, 2016;Tham-Agyekum, 2010). Banks regard agriculture as a very risky business to finance.…”
Section: Promoting a Culture Of Documentation Record Keeping And Datamentioning
confidence: 99%
“…Hewlett (undated) noted that several options exist for handling farm information system; which range from paper forms to be filled by hand to computerised systems. Tham-Agyekum et al (2010) established in a study of 50 poultry farmers in Ga-East Municipality in Ghana that 100% of the respondents kept some form of farm record. Most farmers keep their farm records manually (Jeyabalan, 2010).…”
Section: Records Mode Of Keeping Frequency and Usementioning
confidence: 99%
“…Ryde & Nuthall (1984) Ferrer, et al, (2003) established that 97% of respondents owned computers and applied it for record-keeping among other uses. Tham-Agyekum et al (2010) concluded that a large proportion (82%) of poultry farmers sampled, kept their farm records manually, that is in books, sheets of papers and temporarily on walls to later transfer into record books. Only 2% adopted the computerised system, using mainly Microsoft Office Word and Microsoft Office Excel and 16% tended to use both systems (manual and computerised).…”
Section: Records Mode Of Keeping Frequency and Usementioning
confidence: 99%
See 1 more Smart Citation